2020
DOI: 10.3390/microorganisms8121892
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Dissemination to Humans of Methicillin-Resistant Staphylococcus aureus ST398 through the Pork Production Chain: A Study in a Portuguese Slaughterhouse

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) ST398 was recovered from infections in humans exposed to animals, raising public health concerns. However, contact with food producing chain as a means of transmission of LA-MRSA to humans remains poorly understood. We aimed to assess if pork production chain is a source of MRSA ST398 for human colonization and infection. MRSA from live pigs, meat, the environment, and slaughterhouse workers were analyzed by Pulsed-Field Gel Electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…A predominant spa -type was detected in each abattoir (apart from abattoir B); the predominant spa -type was generally either t011 or t034, types which are both relatively frequently detected in herd level studies of pigs in Europe [ 10 ]. The detection of MRSA in batches of pigs may represent contamination from between batches, from other sources within the abattoir, during transport to the abattoir, or persistence of MRSA in the abattoir after initial introduction, rather than accurately reflecting the status of the farm of origin [ 11 , 12 , 15 , 36 ]. In abattoir E, which was sampled over 2 days, t011 was present on both days possibly suggesting that batches may have been contaminated at the abattoir, which was acting as a reservoir, although t011 tends to be a frequently detected spa -type of MRSA CC398 in pigs in Europe and repeated introduction is equally possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A predominant spa -type was detected in each abattoir (apart from abattoir B); the predominant spa -type was generally either t011 or t034, types which are both relatively frequently detected in herd level studies of pigs in Europe [ 10 ]. The detection of MRSA in batches of pigs may represent contamination from between batches, from other sources within the abattoir, during transport to the abattoir, or persistence of MRSA in the abattoir after initial introduction, rather than accurately reflecting the status of the farm of origin [ 11 , 12 , 15 , 36 ]. In abattoir E, which was sampled over 2 days, t011 was present on both days possibly suggesting that batches may have been contaminated at the abattoir, which was acting as a reservoir, although t011 tends to be a frequently detected spa -type of MRSA CC398 in pigs in Europe and repeated introduction is equally possible.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous European and North American surveillance and research studies have described the occurrence of MRSA at slaughter [9,10], from pigs on arrival [11,12], after stunning [13,14,15], and on carcasses during chilling [16,17]. The majority of the studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from HA- and CA-MRSA infections, the emergence of livestock-associated (LA)-MRSA, especially of the lineage MRSA-CC398, has also caused alarming rates of staphylococcal colonization and infection among humans in contact with livestock, mostly with pigs, suggesting an increased risk of zoonotic transmission [ 14 ]. This MRSA-CC398 lineage could, subsequently, be dispersed to the environment and to other species of animals through the food chain and direct contact [ 15 ]. In this sense, a recent study performed in Spain demonstrated a significant association between the rate of MRSA-CC398 at hospital level and the density of pig farming in the surrounding regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant staphylococci (MRS) emerged in a variety of livestock animals, apparently through different mechanisms (De Boer et al 2009 ). The close proximity amongst humans, livestock and antimicrobial use in animals presumably facilitates the emergence and spread of MRS (Bouchami et al 2020 ). Methicillin-resistant staphylococci have been recovered from various retail products (Bouchami et al 2020 ; De Boer et al 2009 ) leading to an interest in MRS colonisation and infection in animals.…”
Section: Introductionmentioning
confidence: 99%